Does Retirement Get Under the Skin and Into the Head? Testing the Pathway from Retirement to Cardio-Metabolic Risk, then to Episodic Memory. (January 2021) - Oi, Katsuya
Many studies document significant causal impacts of retirement on cognitive abilities. It remains unclear if cognitive functioning could be hindered in post-retirement due to heightened physiological responses to stress. Using repeated observations of biomarkers, retirement status, and the word-recall test score from the Health and Retirement Study (n = 25, 367; 15, 343 among women and 10, 024 among men), the study tests this pathway, separately for men and women. The study employs the two-stage least squares fixed-effects model that simultaneously fits three equations predicting the total-recall score, cardio-metabolic risk index, and retirement status. Being retired for at least a year decreases cardio-metabolic risk for men and women, and the resulting relief of cardio-metabolic risk improves cognitive functioning for women but not for men. Retirement does not lead to a downward health spiral as previously suggested; rather, it provides a much needed relief from stressors for those who are at health risks.